Impact of Sport Education Model on Sports Lifestyle and Attitudes of Vocational Education Training Students - Jorge Giménez-Meseguer; Alberto Ferriz-Valero; Salvador Baena-Morales (Education Sciences, 2022)
The Sport Education Model (SEM) presents a wide background in the teaching of Physical Education and Sport. This is one of the most studied pedagogical models in the last decade in primary and secondary education. However, the studies of this model that are implemented in Vocational Education and Training within the family of Physical Activities and Sports are limited. For this reason, the aim of the present research was to examine the effect of the application of the SEM on motivation and Basic Psychological Needs (BPN). Secondarily, the effect on the social climate of the group, the development of emotions during the intervention, or the students’ perception of possible aspects of improvement of the model were studied. A total of 50 students (19.83 ± 3.20) followed a mixed methodology for 12 sessions. To achieve the objectives, the Spanish version of the Sport Motivation Scale questionnaire and the BPN Measurement scale were used. On a qualitative level, semi-structured interviews were conducted with all participants of the study. The results showed that the SEM was very well accepted by the students, who were fully satisfied with the activity. It was also considered a fun intervention, generating good socio-affective relationships, and was useful and practical for their training as future sports coaches. The intervention seemed to have a positive effect on student motivation, although with inconsistent results in the quantitative analysis of this study. Despite the encouraging results obtained, further research is needed to deepen the effect of SE as a key model in the teaching-learning process.